New radiocarbon dates from prehistoric Non Nok Tha, Don Kok Pho and Don Pa Daeng, upper Nam Phong watershed, Khon Kaen Province, Northeast Thailand. (December 2020) - Conrad, Cyler; Franz, Eden; Green, Ernestene; Jones, Emily Lena
Abstract: Between 1963 and 1964 American and Thai archaeologists, in anticipation of dam and infrastructure development, conducted surveys and salvage excavations in northeast Thailand. Of the archaeological sites identified during their work, three, located along the Nam (River) Phong in Phu Wiang District, Khon Kaen Province proved especially significant. These mound sites, Don Kok Pho (NP6), Non Nok Tha (NP7) and Don Pa Daeng (NP8), were covered in fragments of ceramics, metals, pipes, mollusks and animal bones. Test excavations occurred at all three in 1965, but only Non Nok Tha received systematic excavations in 1966 and 1968. While these excavations at Non Nok Tha were dated using radiocarbon and thermoluminescence techniques, the 1965 test excavations at Non Nok Tha remain undated, as do the excavations at Don Kok Pho and Don Pa Daeng. Here, we report the discovery of two unpublished radiocarbon ages for test excavations at Non Nok Tha and Don Kok Pho, analyzed at the Gakushuin Laboratory, Japan, and six new radiocarbon determinations obtained from additional test excavation samples at these three sites analyzed at the University of Georgia Center for Applied Isotope Studies, Athens, Georgia, USA. Our results from Non Nok Tha align with the previously established chronology for this site. Dates from Don Kok Pho and Don Pa Daeng suggest that these sites are either contemporaneous with or younger than Non Nok Tha. All three sites match the regional Upper Nam Phong Watershed regional chronological sequence. Highlights: Discovery of unpublished radiocarbon dates from Non Nok Tha and Don Kok Pho Analysis of six new radiocarbon dates from 1965 excavations in Khon Kaen Province New ages support currently accepted chronology at Non Nok Tha, northeast Thailand Don Kok Pho and Don Pa Daeng date to the 1st millennium CE Upper Nam Phong Watershed an important prehistoric location in northeast Thailand